The impact of oil shocks on the Spanish economy. - Ana Gómez-Loscos; Antonio Monta\~nes; Maria Dolores Gadea (European Regional Science Association (ERSA), 2010)
This paper analyses the impact of oil both price shocks on the GDP and prices in the Spanish economy and its seventeen NUTS-2 regions. The Qu and Perron (2007) and the Bai and Perron (1998, 2003a and 2003b) methods identify different periods across the sample. Evidence in favour of a diminishing effect of oil price shocks on the output and inflation is found from the 1970s until the mid 1990s. For Spain, the influence of oil shocks recovers some of its initial importance for the GDP in the last part of the 1990s and, especially, for the CPI inflation in the 2000s. The most outstanding result is that the oil price movements could explain at least some of the recent inflation, the main difference between these outcomes and those obtained for the 1970s being the lower value of the impact found in the last part of the sample. For the above mentioned regions, the influence of oil price shocks on the GDP progressively disappears; while the impact on CPI decreases from 1985 on, ten years later it becomes significant again, as in Spain.
Keywords: E31; E32; Q43; C32; 330; oil shocks; inflation; business fluctuations; Spain